Analytical Comparative Study of Some Kinematic Variables Affecting the Distances of 200 m. Freestyle Race - Thamer, Ahmed (Journal of Physical Education, 2020)
The study aimed at identifying some kinematic variables affecting the distances of 200m freestyle race among the swimmers of the Specialized School for Swimming. Three (3) swimmers have been intentionally chosen to be the subjects of the study. The kinematic variables of each player have been extracted by the motor analysis (kinovea) program and their data values then compared. In light of the results, the researcher found out clear big differences in the values of these variables among the swimmers themselves and between each distance of the race distances for each swimmer which led to a big variation in the achievement (final time). A matter that requires reforming procedures in the technical performance and physical characteristics development for the swimmers of the Specialized School in 200m freestyle event in order to reduce the final time (improving achievement).